Referral Rate of Admitted Cardiovascular Patients Eligible for Cardiac Rehabilitation in a Private Level 3 General Hospital: A Three-Year Retrospective Study - Seguban, Joseph Marc S.; Leon, Karen G. Amoloza-De; Barrientos-Regala, Marie A.; Pipo, Michelle Q.; Pestaño, Noemi S.; Punzalan, Felix Eduardo R.; Tumanan-Mendoza, Bernadette A.; Cas, Rafael R. (Cardiology and Cardiovascular Medicine, 2019)
Background: Despite being recommended by most treatment guidelines, referral of eligible cardiovascular patients for cardiac rehabilitation (CR) has been historically poor worldwide. CR-referral rate, which is highly dependent on physician factors, is a performance measure of cardiovascular patient care. In our institution, where cardiovascular cases and interventions are among the most frequent types of cases admitted, data regarding CR referral is limited. Objective: We aimed to determine the CR-referral rate in eligible adult cardiovascular patients admitted to the Manila Doctors Hospital, a tertiary training hospital. Population: All adult in-patients from August 1, 2014 to July 31, 2017, who had acute coronary syndrome (ACS), chronic heart failure (CHF), peripheral artery disease (PAD), percutaneous coronary intervention (PCI), coronary artery bypass grafting (CABG) or valvular surgery. Methods: A descriptive cross-sectional study utilizing chart review. Results: Over-all referral rate was 5.3%. The CR referral rate for CABG was 72%; valvular surgery, 63%; PCI, 3%; ACS, 4%; and CHF, 2%. Trend of referral is increasing among patients who underwent CABG. Among referred patients, 96% were enrolled to Phase I of cardiac rehabilitation only. Conclusion: The CR referral rate of the institution is dismally low at 5.3%. The referral rate is higher for CABG and heart-valve surgery patients than those undergoing PCI. Referral trend is increasing in CABG patients. Enrollment rate to Phase I cardiac rehabilitation was 96%; Phase II, 16%; and Phase III, 2%.